Effects of boron and nitrogen on grain yield and on nutrients level in the plant of irrigated wheat, in the brazilian cerrado region - da Silva, Dijalma Barbosa (Pesquisa Agropecuaria Brasileira, 1992)
Tlte effects of boron (B) and nitrogen (N) on irrigated wheat (Triticun aestivum L.) crop were evaluated under field conditions in a ctay Dark-Red Latosol, in a cerrado arca of Brazil. The experimental design was a 3 x 4.factoríal in a complete randomized block design, with four levels of B (0, 1, 3 a 6 kg/ha), and three levels of N (0, 60 and 120 kg/ha) and three replicates. B (borax) was broadcasted before seeding and N (urea) was topdressed at the tillering stage. No effect of B neither of N was observed on grain yield, number of grains/spike, and the leaf content of N, P, K and Ca. Aplication of 3 kg/ha.of B promoted higher concentration of Mg in leaves. Increasing of B and N levels promoted increase of B concentration in leaves. Male sterility as welt as phytotoxic effects were not observed.